THE INFLUENCE OF THE XV TH CENTURY SAMARKAND SCIENTIFIC SCHOOL ON THE DEVELOPMENT OF EASTERN AND WESTERN RATIONAL THINKING - Hamdamov Islоm Akramovich (Journal Park Publishing, 2023)
In this article, the contribution of the 15th century Samarkand High School to world science, including logic, astronomy, mathematics, and natural science, is widely acknowledged. It was also noted that Mirzo Ulughbek used his rational philosophical views in his scientific work, and that empirical knowledge was central to knowledge, understanding, thinking and drawing conclusions in his philosophical views.
Keywords: exact sciences, empirical and rational knowledge, philosophy, history, logic, astronomy, mathematics, natural sciences.